Does the home environment influence inequalities in unintentional injury in early childhood? Findings from the UK Millennium Cohort Study. Issue 2 (14th October 2011) - Pearce, A; Li, L; Abbas, J; Ferguson, B; Graham, H; Law, C
Abstract : Background: Children from disadvantaged backgrounds are more likely to experience unintentional injuries and poor home environments. The aim of this study was to explore the home environment as a potential mediator between socioeconomic circumstances and unintentional injuries, in the UK Millennium Cohort Study (n=14 378). Methods: RRs and 95% CIs for being injured in the home between age 9 months and 3 years were estimated according to four measures of socioeconomic circumstances: social class, maternal education, lone parenthood status and tenure. Proxy indicators of housing quality (build type, storey, garden access, rooms per capita, central heating and presence of damp) and safety equipment use (use of fireguards, safety gates, electric socket covers and smoke alarms) were then controlled for in order to observe potential mediation. Results: Children from routine and manual backgrounds were more likely to be injured than those from managerial and professional backgrounds (RR=1.33, 95% CI 1.21 to 1.47), as were children of lone parents (compared with couple families) (RR=1.23, 95% CI 1.12 to 1.36), those whose mothers had no educational qualifications (compared with a degree) (RR=1.42, 95% CI 1.24 to 1.63) and those living in socially rented accommodation (compared with owned/mortgaged homes) (RR=1.35, 95% CI 1.24 to 1.46). However, controlling for the indicators of housing quality and safety equipment use did not alter the elevated risk of injury experienced by children from less advantaged backgrounds. Conclusions: In this contemporary UK cohort, proxy indicators of the home environment did not appear to explain socioeconomic inequalities in injuries. Research exploring alternative explanations for inequalities in injuries could help contribute to the design or adaptation of policies to reduce them.